(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The pulse value chain played significant role in agriculture and other industry sector such as food , pharma industry. The pulse value chain consists of sequences of business activities that perform significant activities, from primary production transformation into the final product to marketing for final consumption to the consumer. Pulse value chain develops different framework structures for developing competitive business strategy development to identify the significant constraints in a compressive manner. However, pulse processing firms face many risks, i.e., production risk, operation risk, supply risk, etc., which hampers the growth of these firms. The paper aims to identify pulse processing firms' risk factors and measure the severity of the risk. The risk assessment of pulses processing firms creates the opportunity for continuous quality improvement of the pulse value chain, and their performance also develops quality up gradation of pulse processed food. The present study is based on 25 pulse processing firms selected firms from the states of Uttar Pradesh, Rajasthan, and Delhi/NCR. The study applied FMEA (Failure mode Effect Analysis) and Pareto Analysis to identify the potential risk and determine their severity index with the help of the Pareto analysis chart, and applied the ANOVA method to generate the frequency of F- the value of risk factors impact on pulse firms understand the level of significance of risk factors.